2011
DOI: 10.1105/tpc.111.084608
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Class I KNOTTED-Like Homeobox Proteins Act Downstream in the IDA-HAE/HSL2 Floral Abscission Signaling Pathway

Abstract: Floral organ abscission in Arabidopsis thaliana is regulated by the putative ligand-receptor system comprising the signaling peptide INFLORESCENCE DEFICIENT IN ABSCISSION (IDA) and the two receptor-like kinases HAESA and HAESA-LIKE2. The IDA signaling pathway presumably activates a MITOGEN-ACTIVATED PROTEIN KINASE (MAPK) cascade to induce separation between abscission zone (AZ) cells. Misexpression of IDA effectuates precocious floral abscission and ectopic cell separation in latent AZ cell regions, which sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
169
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(187 citation statements)
references
References 66 publications
(126 reference statements)
18
169
0
Order By: Relevance
“…This set of cellular characteristics is reminiscent of meristematic tissues. Several genes involved in SAM maintenance and the initiation of axillary meristems are expressed in the AZ (Shi et al, 2011;Nakano et al, 2013;Wang et al, 2013). Therefore, it has been proposed that AZ cells have a meristematic identity.…”
Section: Osh15-qsh1 Dimer Functions For Az Developmentmentioning
confidence: 99%
“…This set of cellular characteristics is reminiscent of meristematic tissues. Several genes involved in SAM maintenance and the initiation of axillary meristems are expressed in the AZ (Shi et al, 2011;Nakano et al, 2013;Wang et al, 2013). Therefore, it has been proposed that AZ cells have a meristematic identity.…”
Section: Osh15-qsh1 Dimer Functions For Az Developmentmentioning
confidence: 99%
“…2 and 3). In Arabidopsis, during the last step of petal senescence, abscission, the expression of BREVIPEDICELLUS (BP)/ KNAT1 is induced, and the accelerated petal abscission phenotype of its knockout mutant, bp, indicates that BP/KNAT1 plays an antagonistic role in the petal abscission process (Shi et al, 2011). It has also been shown that in sunflower, increased expression of HaHB-4 suppresses flower senescence (Manavella et al, 2006).…”
Section: Rhpr101 Is Involved In Ethylene-induced Rose Petal Senescencementioning
confidence: 99%
“…A mitogen-activated protein kinase (MAPK) cascade consisting of MITOGEN-ACTIVATED PROTEIN KINASE KINASE 4/5 (MKK4/5) and MPK3/6 is positioned genetically downstream from HAE/HSL2 (8). Mutations in the transcription factor BREVIPEDI-CELLUS (a knotted1-like homeobox transcription factor) suppress the abscission defect of the hae hsl2 double mutant (10). Additionally, nevershed (nev; an ARF-GAP domain protein) plants do not abscise, whereas secondary mutations in evershed [evr; a leucine-rich repeat (LRR) receptor-like protein kinase], somatic embryogenesis receptor kinase1 (a LRR receptor-like protein kinase), and cast away (a receptor-like cytoplasmic protein kinase) suppress the abscission defect of nev (11)(12)(13)(14).…”
mentioning
confidence: 99%